Genetic parameters for production and feeding behaviour traits in crossbred steers fed a finishing diet at different ages - Durunna, O.N.; Mujibi, F.D.N.; Nkrumah, D.J.; Basarab, J.A.; Okine, E.K.; Moore, S.S.; Wang, Z. (Agricultural Institute of Canada, 2013)
Because cattle can be raised postweaning under several feeding regimes, this study examined the consistency of phenotypic and genetic parameters of some production and feeding behaviour traits between two feeding periods that beef cattle received a finisher diet. Crossbred steers (n = 851) were used for feeding trials from 2002 to 2009 where the steers received a finisher diet either during the fall-winter season (FP1) or during the winter-spring season (FP2). The steers evaluated in FP2 received a backgrounding diet in FP1. Traits examined include dry matter intake (DMI), average daily gain (ADG), gain: feed ratio (G:F), residual feed intake (RFI), and ultrasound measures of backfat thickness (UBF), ribeye area (UREA) and marbling (UMB). Others include feeding duration (FD), headdown time (HDT) and feeding frequency (FF). As expected, there was no difference (P = 0.90) between the RFI measured in the two periods. The two periods were similar for UBF (P = 0.87) and UREA (P = 0.25),while DMI, ADG and UMB were greater (P<0.04) in FP2 than in FP1. The FD, HDT and FF were greater (P <0.0001) in FP1 compared with FP2. Heritability estimates were calculated in FP1 and FP2, respectively, for ADG (0.38, 0.28), DMI (0.52, 0.42), RFI (0.16, 0.27), G:F (0.18, 0.33), HDT (0.35, 0.18) and FF (0.26, 0.46). More importantly, genetic correlations between FP1 and FP2 were estimated for DMI (0.61), RFI (0.65) and G:F (0.60). The results may indicate the influence of age or feeding period or both on these traits, which may suggest the need for multi-environment genetic evaluations to identify superior animals.